Acute effect of concurrent training on hematological and hepatic profile, and muscle injury markers in trained individuals - Guilherme Rosa; Danielli Mello; Rodrigo Gomes de Souza Vale; Giullio César Pereira Salustiano Mallen da Silva; Claudio Melibeu Bentes; Fabrizio Di Masi; Ravini Sodré; Norma Cláudia de Macedo Souza Santos; Marcos Fortes; Estélio H. M. Dantas (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: to analyze the acute effect of concurrent training on hematological and hepatic profile, and muscle injury markers in trained individuals.